The Influence of Complaint Handling and Brand Image on Consumer Satisfaction and Loyalty (A Study of Azarine Overclaim Skincare Product Consumers in Lawang District) - Nur Fitri, Aisya; Rohmad Nuzil, Nur (CV. Satria Jaya, 2025)
The Influence of Complaint Handling, Brand Image on Consumer Satisfaction and Loyalty (Consumer Study of Azarine Overclaim Skincare Products in Lawang District). This study aims to determine the influence of complaint handling and brand image on consumer satisfaction and loyalty (a study of Azarine Overclaim Skincare Consumers in Lawang District). This study uses explanatory research with a quantitative approach and uses questionnaires as data collection techniques. The sampling method uses non-random sampling. The sample used was 116 respondents. The data analysis method used in this study is the Partial Least Square (PLS) test tool. The results of this study indicate that Complaint Handling has a positive and significant influence on Consumer Loyalty based on p-value 0.008 (<0.05), then H1 is accepted and H0 is rejected. Complaint Handling has a positive and significant influence on Consumer Loyalty based on p-value 0.000 (<0.05), then H2 is accepted and H0 is rejected. Brand Image has a positive and significant influence on Consumer Satisfaction based on p-value 0.000 (0.05), then H3 is accepted and H0 is rejected. Brand Image has a positive and significant influence on Consumer Loyalty based on p-value 0.000 (0.05), then H4 is accepted and H0 is rejected. Consumer Satisfaction has a positive and significant influence on Consumer Loyalty based on p-value 0.037 (<0.05), then H5 is accepted and H0 is rejected.